Experimental study on impact behaviour of steel plane tubular frames. (February 2017) - Qu, Hui; Huo, Jingsi; Li, Anling; Jiang, Yan; Liu, Yanzhi
Abstract: This paper experimentally examines the dynamic behaviour of two steel plane tubular frames subjected to impact loading with the same impact energy. One specimen is set up to be hammer impacted on the mid-span section of the top chord between two K-joints, while another is loaded on the mid-span section of the top chord within the middle K-joint. The dynamic response of both frames are described and discussed with emphasis on the effect of impact-loading locations. Based on the experimental results, the key deformation patterns, the time history of impact force, deformation and strain are identified. The two specimens suffer significant local indentation at impacted zone, the deflection of impacted chord between two joints and the global flexural deformation of the whole frame. Moreover, the impact mechanism and energy dissipation is also investigated to evaluate the impact resistance of steel tubular frames. Additionally, based on the plastic hinge line theory, a simplified calculation method of energy dissipation is proposed and verified against the experimental result. The studies in this paper also provide basis data for future anti-impact design of steel tubular structures. Highlights: Plastic deformation mainly concentrated on local indentation of chord or joint. Impact energy was dissipated by local indentation and flexural deformation. The NORSOK standard method can be used to estimate the impact response. A simplified method was developed to calculate the energy dissipation.